Validated TLC-densitometry method for determination of cetirizine dihydrochloride in tablet dosage form - Kristiningrum, Nia; Martyanti, Ellsy Novita (International Current Pharmaceutical Journal, 2013)
A rapid, reproducible and accurate TLC method was developed for the determination of Cetirizine Dihydrochloride in tablet. The analytes were dissolved with ethanol 70% and chromatographed on silica Gel GF 254 TLC plate using chloroform : methanol : ethyl acetate in the ratio of 2 : 7 : 3 (v/v) as mobile phase. Quantitative analysis was done through densitometric measurement at wavelength 234 nm. Method was found linear over the concentration range of 400 1600 ng/spot with the correlation coefficient of 0.996. Specificity showed calculation of purity and identity more than 0.99. The limit of detection (LOD) and the limit of quantification (LOQ) of the method were 75.54 and 226.64 ng/spot. The relative standard deviation of this method was 0.86% whereas the means of the recovery data was 100.54 ± 0.11%. The proposed method has been applied to the determination of Cetirizine Dihydrochloride in commercial tablet formulations and the result were 96.97 ± 0.86 % for brand A and 100.57 ± 1.17 % for brand B. The developed method was successfully used for the assay of Cetirizine Dihydrochloride. This method is simple, sensitive and precise; it can be used for the routine quality control testing of marketed formulations. DOI: http://dx.doi.org/10.3329/icpj.v3i1.17294 International Current Pharmaceutical Journal, December 2013, 3(1): 208-210